A study on family planning acceptance among slum dwellers in Shillong, Meghalaya - Dey, Sanku (Indian Journal of Community Health, 2014)
Background: Despite the fact that contraceptive usage has increased over a period of time, there exists a Knowledge Attitude and Practice-gap regarding contraception. There are multiple reasons for not using any family planning methods, current study attempts to explore these reasons. Aims: To study the family planning practices/methods among the married women of reproductive age groups. Study Design: Community-based cross-sectional study. Study Subjects: The Women of reproductive age groups adopting family planning methods & those residing in urban slums of Shillong city. Sample size: 1417. Study Period: April 2010 to March 2012. Sampling Technique: Two-stage random sampling. Results: Overall, the contraceptive prevalence rate (CPR) was 38. The contraceptive use is high among women who have two to three surviving children (37.1 percent). Majority of the women who were adopting any of the family planning method belonged to the age group 18-24 years. Women’s education and occupation are important determinants that demonstrate highly significant positive relationships with any contraceptive use in the slum-dwelling women of Shillong city. Sex composition of living children also appeared to be significant determinant factor for contraceptive use. Monthly family income is also an important determinant of contraceptive use in slums of Shillong city. Conclusions: The elder women were more reluctant in contraceptive use than their younger counterparts. Sterilization is the most accepted one among all the contraceptive methods.